Analisis Kinerja Pembiayaan UMKM pada Bank Syariah di Indonesia - Bernad Hananto; Andi Suhandi; Azmy Muhammad Habiby (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy, contributing to increased income and well-being. This study aims to analyze the performance of MSME financing at Bank Syariah Indonesia over the past decade, as well as the economic and financial factors influencing non-performing financing. This study uses a trend analysis of NPF (Non-Performing Financing) through visual graphs, descriptive statistics, and breakpoint analysis. Furthermore, linear regression analysis is used to examine the effects of inflation, interest rates, GDP, and exchange rates on NPF. The results show that MSME NPF at Islamic banks has improved, and GDP significantly influences NPF, where a 1% increase in GDP is followed by a 0.89% decrease in NPF. Meanwhile, inflation and interest rates do not directly affect NPF, although interest rates can influence GDP and the ability of MSMEs to meet funding obligations.